A produção das identidades profissionais de jovens do campo pela pedagogia da alternância no interior de Rondônia (Revista Cocar, 2019)
The production of professional identities of rural youth by the pedagogy of alternation in the countryside of RondoniaResumoO artigo objetivou analisar o processo de produção das identidades profissionais, produzidas pela Pedagogia da Alternância no espaço educativo do Centro Familiar de Formação por Alternância (CEFFA) de Ji-Paraná em Rondônia, que recebe jovens do campo de dezoito municípios do interior do Estado. O trabalho recorre ao campo teórico dos Estudos Culturais pós-estruturalistas, principalmente às ideias de autores que concebem as identidades como contingentes, plurais. Como procedimento metodológico para a investigação, fez-se uso da entrevista com alunos e monitores, da observação do contexto escolar, além da análise de documentos curriculares. O estudo mostrou que a Pedagogia da Alternância, tendo em vista sua ambivalência, produz por meio de suas práticas sociais, identidades profissionais competentes, qualificadas sempre em movimento.Palavras-chave: Pedagogia da Alternância. Estudos Culturais. Identidades profissionais. Abstract The present essay aimed to analyze the process of production of professional identities, developed by the Pedagogy of Alternation at the Familiar Center of Training by Alternation (known in Brazil by the Portuguese acronym CEFFA) in the city of Ji-Parana, Rondonia, which receives rural youth students from eighteen cities of Rondonia State countryside. The essay goes through the theoretical field of post-structuralist cultural studies, mainly to the ideas of authors who conceive identities as contingent, plural. As a methodological procedure for the investigation, it was chosen the use of interview with students and school monitors, observing the school context and analyzing curricular documents. In view of its ambivalence, the study showed that the Pedagogy of Alternation produces competent and qualified professional identities by means of its social practices and they are always under development.Keywords: Pedagogy of Alternation. Cultural Studies. Professional Identities